Evaluation of physical characteristics and sensory acceptance of newly developed vegetable-based soups - Lim, Sim Yee; Rosmawati, Dora; Yatiman, Noor Hafizah; Wong, Jyh Eiin; Haron, Hasnah; Poh, Bee Koon (Progress in Nutrition, 2022)
The average vegetables consumption of Malaysian children is relatively low and do not meet the recommendations set by Malaysian Dietary Guidelines. Serving vegetables in the form of blended soup may increase vegetable consumption among children. This study aimed to evaluate physical characteristics of newly developed vegetable-based soups and their sensory acceptance by Malaysian children from three main ethnicities. Three different soups were prepared by blending potatoes with different ratios of carrots, celery and leek. Soup A was made with 25 g of each type of vegetable, soup B was made by doubling the amount of vegetables used in A, and soup C was the same as soup B but with 50% more carrots. In terms of colour measurement, the L* value was significantly lower (p<0.05) in soup C than soups A and B, whereas the colour intensity of redness (a*) and yellowness (b*) was significantly higher (p<0.05). Mean sensory scores for attributes of colour, saltiness, sweetness and overall acceptance were highest for soup C. For the attribute of taste, mean score of soup C (5.4±2.2) was significantly higher (p<0.05) than that for soup A (3.3±2.0) among Malays, while no significant differences (p>0.05) were observed among Chinese and Indians. In conclusion, the vegetable soup with extra carrots was well-accepted by children from all three ethnicities and may be adopted as a dietary strategy to increase children’s vegetable intake.